THE ROLE OF THE SPECIAL DEVELOPMENT INSTITUTIONS OF CHILDREN CLASS I KUPANG IN THE RE-EDUCATION PROCESS LEGAL CONFLICT CHILDREN - Mikayani Putri; Satria Akbar; Evelyn B. Sumby; Chrisna Kurnia Miha Balo (Legal Standing : Jurnal Ilmu Hukum, 2020)
Writing of this Thesis aims to find out the legal position and the role of the Special Guidance Institution for Children in the Criminal Justice System, the scope of childdevelopment and re-education of children in conflict with the law, As for thebackground of writing that the number of children in conflict with the law in 2019 hasincreased a total of 32 children in 2018 or from 9 children to 41 children who arefostered. Likewise, the number of children in conflict with the law in 2018 has increasedby 8 children in 2017 or from 1 child to 9 children. From this condition, learning takesplace about the actions that need to be taken in rder to survive in the midst of difficultconditions. This study uses a normative juridical approach which means that inanalyzing the problem carried out by combining legal materials (which are secondarydata) with primary data obtained in the field, namely on the Role of the Kupang Class IChild Special Development Institution in the Process of Re-Education of Children TheConflict of Laws. The results showed that the position of the Kupang I Class SpecialChild Coaching Institution in fostering Children in Conflict of Laws was in accordancewith the unity of the concept of the Criminal Justice System, namely providing guidancein accordance with Pancasila, the 1945 Constitution, the main principles ofcorrectional and penification services that have been determined in the Law.Penitentiary Law No. 12 of 1995. In addition, in the procedure and re-educationprocess of Children in Conflict of Law, at least through 4 stages, namely theintroduction of the environment, 0 to 1/3 criminal period, 1/3 criminal until the ½criminal period and Assimilation